Helping mentors address scientific communication in STEM research training helps their mentees stay the course - C. Cameron; H. Y. Lee; C. B. Anderson; E. K. Dahlstrom; S. Chang (SpringerOpen, 2024)
Abstract Background Scientific communication (SC) has important social-cognitive, behavioral, and career-related benefits for emerging researchers, but both mentors and mentees find development of SC skills challenging. Whether training mentors to effectively mentor development of SC skills could have a meaningful impact on mentees was not clear. The Scientific Communication Advances Research Excellence (SCOARE) project has conducted faculty training workshops in techniques for mentoring SC skills since 2018. To study indirect workshop effects of mentors' attendance at the SCOARE workshop on their matched PhD and postdoctoral mentees (N = 477), we surveyed mentees before and 6 months after their mentors attended and measured their social-psychological and behavioral outcomes. To examine the effectiveness of the workshop and to explore whether workshop effects vary based on mentee demographic characteristics, including home language variety (speaker of standardized English [STE], non-standardized English [NSTE], or another language [L2]), we conducted multilevel models. Results After adjusting baseline scores, mentees of mentors who attended SCOARE workshops (W +) were more engaged in speaking activities (β =0 .30, p = 0.016), had higher science identity (β = 0.20, p = 0.048), and were less likely to reconsider their career due to SC skills (β = - 0.39, p = 0.004) than mentees in the W- group. Across demographic groups, mentees of mentors who attended SCOARE workshops showed similar improvements in SC outcomes. Postdoctoral mentees, compared to doctoral mentees, had higher science identity and lower intention to pursue a non-research-intensive career. Comparing mentees of the 3 categories of home language variety, both the NSTE and L2 groups, compared to the STE group, were more likely to reconsider their careers due to SC skills and had a higher intention to pursue non-research-intensive careers both at baseline and post-workshop, suggesting the possibility of language background as a barrier to mentee career progression. Conclusion Mentor training for SC skill development can improve social-psychological and behavioral outcomes for mentees, including science identity, frequency of speaking, and reconsideration of research careers due to concerns about SC.